PENGARUH MARKETING MIX TERHADAP PENGAMBILAN KEPUTUSAN PEMBELIAN PRODUK MELALUI E-COMMERCE OLEH MAHASISWA DI STIA ASUH MITRA SOLO - Widyowati, Luky; Slamet, Giarti (Surakarta Management Journal, 2021)
In this study, the authors have goals to be achieved in this study are 1) Knowing and explaining the significant influence of products on purchasing decisions through e-commerce at STIA ASUH MITRA Solo; 2) Knowing and explaining the significant influence of price on purchasing decisions through e-commerce at STIA ASUH MITRA Solo; 3) Knowing and explaining the significant effect of promotion on purchasing decisions through e-commerce at STIA ASUH MITRA Solo; 4) Knowing and explaining the significant influence of place/distribution channel on purchasing decisions through e-commerce at STIA ASUH MITRA Solo; 5) Knowing and explaining the significant influence of products, prices, promotions, and distribution channels on purchasing decisions through e-commerce at STIA ASUH MITRA Solo               The hypotheses in this study are 1) Products have a significant influence on purchasing decisions through e-commerce at STIA ASUH MITRA Solo; 2) Price has a significant influence on purchasing decisions through e-commerce at STIA ASUH MITRA Solo; 3) Promotion has a significant influence on purchasing decisions through e-commerce at STIA ASUH MITRA Solo; 4) Distribution channels have a significant influence on purchasing decisions through e-commerce at STIA ASUH MITRA Solo; 5) Products, prices, promotions, and places/distribution channels have a significant influence on purchasing decisions through e-commerce at STIA ASUH MITRA Solo            The results of data analysis in this study can be concluded that 1) the product has a significant positive effect on purchasing decisions. It is proven by the coefficient value is positive (0.074>0) and the probability value is (0.048<0.05; 2). Price has a significant positive effect on purchasing decisions. It is proven by the coefficient value is positive (0.266>0) and the probability value is (0.002 < 0.05 3). Promotion has a significant positive effect on purchasing decisions. It is proven by the coefficient value is positive (0.146>0) and the probability value is (0.021<0.05 4). Distribution channels have a significant positive effect on purchasing decisions. It is proven by the coefficient value is positive (0.259>0) and the probability value is (0.002<0.05).